2011
DOI: 10.1073/pnas.1101707108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular in situ topology of Aczonin/Piccolo and associated proteins at the mammalian neurotransmitter release site

Abstract: The protein machinery of neurotransmitter exocytosis requires efficient orchestration in space and time, for speed and precision of neurotransmission and also for synaptic ontogeny and plasticity. However, its spatial organization in situ is virtually unknown. Aczonin/Piccolo is a putative organizer protein of mammalian active zones. We determined by immunogold electron microscopy (EM) (i) the spatial arrangement (i.e., topology) of 11 segments of the Aczonin polypeptide in situ, and correlated it to (ii) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 50 publications
6
82
1
Order By: Relevance
“…2). Two studies (tom Dieck et al, 2005;Limbach et al, 2011) reported Munc13-1 expression at photoreceptor ribbon synapses (but see Schmitz et al, 2001). An explanation for these findings is that the antibodies used there detected both Munc13-1 and ubMunc13-2, since Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Two studies (tom Dieck et al, 2005;Limbach et al, 2011) reported Munc13-1 expression at photoreceptor ribbon synapses (but see Schmitz et al, 2001). An explanation for these findings is that the antibodies used there detected both Munc13-1 and ubMunc13-2, since Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…1B,C, illustrating the crossreactivity of the polyclonal anti-Munc13 antibody with Munc13-1, Munc13-2, and Munc13-3), or against the N terminus of Munc13-1 (Limbach et al, 2011), which is highly homologous to ubMunc13-2. Indeed, the latter study acknowledges significant cross-reactivity of the antibody used with ubMunc13-2 (Limbach et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, sequence alignment shows a very weak homology of SO to the proteins of aczonin/piccolo family. In mammalian synapses, these proteins are thought to regulate the transition of neurotransmitter-loaded vesicles from the reserve to the release-ready pool and thus are involved in the coordination of rapid fusion of multiple vesicles [56].…”
Section: Mak-2 Could Regulate Both Docking and Fusion Of Secretory Vementioning
confidence: 99%
“…The CAZ is an electron-dense region in electron micrographs and integrates many proteins that regulate neurotransmitter secretion in presynaptic terminals. Piccolo and its interacting proteins are positioned to support synaptic vesicle supply to the site of release and support synaptic reliability during intense activity (Limbach et al, 2011). The Piccolo protein consists of two Zinc-finger, one PDZ, three-coiled coil, and two C2 domains (C2A and C2B).…”
Section: Introductionmentioning
confidence: 99%